1998
DOI: 10.1046/j.1365-2621.1998.00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a ‘quinone‐trapping’ substance from a crude Carica papaya protein preparation

Abstract: The oxidation of different phenols [4‐methylcatechol, chlorogenic acid, (−)‐epicatechin and (+)‐catechin] by endive polyphenoloxidase (PPO) was investigated in the presence of an extract from Carica papaya. The occurrence of cysteine and another ‘quinone‐trapping’ substance in the extract was demonstrated. The unknown substance was purified, as a 4‐methylcatechol conjugate form, by a combination of Bio‐gel Pz chromatography and semipreparative high‐performance liquid chromatography (HPLC). Use of liquid chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…2005). PPO catalyzes mono‐ and o ‐diphenol conversion to o ‐quinones during ripening and during postharvest handling, storage and processing (Richard‐Forget et al. 1998; Nkya et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2005). PPO catalyzes mono‐ and o ‐diphenol conversion to o ‐quinones during ripening and during postharvest handling, storage and processing (Richard‐Forget et al. 1998; Nkya et al.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme PPO (EC 1.10.31) is found in the tissue of a wide range of fruits and vegetables, and is responsible for the browning discoloration observed in many plant food materials (Dry and Robinson 1994;Broothaerts et al 2000;Chen et al 2000;Okot-Kotber et al 2002;Leja et al 2003;Yang et al 2004;Casado-Vela et al 2005). PPO catalyzes mono-and o-diphenol conversion to o-quinones during ripening and during postharvest handling, storage and processing (Richard-Forget et al 1998;Nkya et al 2003;Casado-Vela et al 2005;Selles-Marchart et al 2006;Spagna et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These products do not aect the oxygen uptake, but react with the 4-methylcatechol oxidation products as reported by Richard-Forget et al (1998). This lag phase is caused by cysteine and a dipeptide (glutamic acid±cysteine) in the commercial papaya latex preparation.…”
Section: Ppo Inhibition By the Papaya Latex Preparationmentioning
confidence: 66%
“…Thus, low molecular weight compounds exhibiting PPO-inhibitory properties have been detected in cultures of Dactylum dendroõÈ des (Harel et al, 1967), in potato (Nilova et al, 1973) and mushroom (Madhosingh, 1975) extracts. Richard-Forget et al (1998) have demonstrated that commercial papain preparations (from papaya latex) contain some substances which act as`quinone-trapping' materials. Tan & Harris (1995) found that products of the Maillard reaction inhibited apple PPO; similar observations were made by Tong et al (1995) with pectin preparations.…”
Section: Introductionmentioning
confidence: 99%